Convergent Evolution of Claw Shape in a Transcontinental Lizard Radiation. (7th November 2019) - Baeckens, Simon; Goeyers, Charlotte; Van Damme, Raoul
Abstract: Species occupying similar selective environments often share similar phenotypes as the result of natural selection. Recent discoveries, however, have led to the understanding that phenotypes may also converge for other reasons than recurring selection. We argue that the vertebrate claw system constitutes a promising but understudied model system for testing the adaptive nature of phenotypic, functional, and genetic convergence. In this study, we combine basic morphometrics and advanced techniques in form analysis to examine claw shape divergence in a transcontinental lizard radiation (Lacertidae). We find substantial interspecific variation in claw morphology and phylogenetic comparative statistics reveal a strong correlation with structural habitat use: ground-dwelling species living in open areas are equipped with long, thick, weakly curved, slender-bodied claws, whereas climbing species carry high, short, strongly curved, full-bodied claws. Species occupying densely vegetated habitats tend to carry intermediately shaped claws. Evolutionary models suggest that claw shape evolves toward multiple adaptive peaks, with structural habitat use pulling species toward a specific selective optimum. Contrary to findings in several other vertebrate taxa, our analyses indicate that environmental pressures, not phylogenetic relatedness, drive convergent evolution of similarly shaped claws in lacertids. Overall, our study suggests that lacertids independently evolved similarly shaped claws as an adaptation to similar structural environments in order to cope with the specific locomotory challenges posed by the habitat. Future biomechanical studies that link form and function in combination with genomic and development research will prove valuable in better understanding the adaptive significance of claw shape divergence.